2017
DOI: 10.3892/etm.2017.4329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the hemodynamics and dynamics of fluid shift of Ringer's solution before surgery in children and adults

Abstract: Abstract. The present study investigated the hemodynamics, vascular and extravascular volume expansion induced by infusion of lactated Ringer's solution in children and adults before surgery. This was a prospective randomized double-blind study. A total of 28 patients (14 children and 14 adult patients; American Society of Anesthesiology status I) scheduled for similar minor pelvic, anal rectal or lower limb surgery were recruited for the present study. All patients were administered with 10 ml/kg of lactated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In this study, even at 120 min post-infusion, the VEE was still more than 20%, indicating that the distribution balance of crystalloid (1:4 distribution rule) was not reached. In another our previous study, 18) VEE was less than 100% after RL infusion and before anesthesia induction for minor surgery in both adults and children. VEE reached a distribution balance of 1:4 at 30 mins post-infusion in children and at 90 mins post-infusion in adults.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In this study, even at 120 min post-infusion, the VEE was still more than 20%, indicating that the distribution balance of crystalloid (1:4 distribution rule) was not reached. In another our previous study, 18) VEE was less than 100% after RL infusion and before anesthesia induction for minor surgery in both adults and children. VEE reached a distribution balance of 1:4 at 30 mins post-infusion in children and at 90 mins post-infusion in adults.…”
Section: Discussionmentioning
confidence: 69%
“…Our previous studies 3,4) indicated that the volume expansion of infused crystalloid was more than 1:1 on some certain occasions, such as during anesthesia, at early times of infusion and with low blood volume. Multi-factor regression found that hypotension was an independent factor for increased volume expansion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations